Identificación de conglomerados (clusters) para implementar objetos de software (Identification of clusters in order to implement software objects) - Prieto de Hoyos, Manuel (Facultad de Contaduría Pública y Administración U.A.N.L., 2010)
Abstract: This work presents a study about an entrepreneurial information commercial system which identifies data clusters which allow recognizing software objects that may be implemented in a entrepreneur framework. This study proposes a classification attending the function of the objects, normality tests are conducted over the data in order to proof the data clusters existence. Finally new steps in the research are suggested to develop the objects found.